Augmented Reality for Education: A Bibliometric Analysis Using VOSviewer: Augmented Reality untuk Pendidikan: Analisis Bibliometrik Menggunakan VOSviewer - Astuti, Rina (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
This review aims to present a comprehensive knowledge mapping and analysis of Augmented Reality in education by conducting bibliometric analysis. This study will provide insight into the scope of research, the most frequently emerging research trends, and other areas in education. The use of AR in education has become an interesting topic for researchers over the past few years, presenting significant progress and transformation in educational technology that can improve students' understanding in the learning process. The data was taken from the Scopus database which discusses the use of Augmented Reality in the field of education and found 1396 journal articles. Based on the results of VOSviewer data processing with the topic of augmented reality in education, 4,2561 keywords were found. and related keywords were limited to 9 keywords. and 103 related keywords were found. Bibliometrics can improve the understanding of augmented reality and provide many contributions by discussing keywords used in the literature and grouping research trends and providing directions for further research.